Pembuatan Portal Web SMKN 6 Mataram Sebagai Media Promosi dan Informasi Kelulusan Siswa - Muhamad Azwar; Moch. Syahrir; Pahrul Irfan (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
A website is a collection of interconnected, publicly accessible Web pages that share a single domain name. Websites can be created and maintained by individuals, groups, businesses, or organizations to serve a variety of purposes, such as the rapiddelivery of information to the public. Websites come in almost endless variations, including educational sites, news sites, forums,social media sites, e-commerce sites, and so on. The pages on a website are usually a mixture of text and other media. There are no rules that determine the form of the website, one example is a website for schools which is one of the most effective mediafor delivering graduation information or information related to schools, especially at SMK Negeri 6 Mataram where students do notonly come from within the region but there are also those from outside the region so that this is one of the school's challenges to create an intermediary medium for delivering information nationally. Previously, SMK Negeri 6 Mataram in conveying graduation information to students still used paper and envelopes given to students as well as posting information on the wall magazine because it was too wasteful. and there are restrictions on the delivery of information. So that SMK Negeri 6 Mataramenforces thedelivery of graduation information by using a website so that it can be accessed by students in various places, so as to reduce the use of paper and envelopes, the website is built using a combination of codeigniter and Laravel frameworks in order to reduce hacking from irresponsible parties